Product Design of Portable Oscilloscope Using Arduino to Analyze Signal - Wildan Maulana; Nyoman Bogi Aditya Karna; Ridha Muldina Negara (eProceedings of Engineering, 2020)
An electrical signal is an electrical voltage or current that carries information. The term electrical signal in a circuit can refer to voltage or current. Voltage or often people call with potential differences, is the energy carried out to move a single charge, while an electric current is a change in the speed of a charge with respect to time or charge that flows in units of time. In a research or scientific project, measurement tools are often needed that can project the form of electrical signals to be seen and studied. One measuring instrument commonly used is the oscilloscope (oscilloscope). Oscilloscopes are usually used to observe the exact wave shape of an electrical signal. This measuring instrument works based on data samples, the higher the data sample, the more accurate the electronic equipment. Oscilloscopes usually have very high data samples, so Oscilloscopes are very expensive electronic measuring devices. If an oscilloscope has a sample rate of 10 Ks / s (10 kilos of sample / second = 10,000 data per second), then this tool will read 10,000 times a second. However, not all scientific research or projects require a type of Oscilloscope that has such a high level of accuracy, there are some of them needed just to learn a basic introduction to electrical signals, there are several other cases needed to be practically portable, so it is easy to use at the time is required. But in the market today, Oscilloscope products are dominated by products of manufacturing manufacturers with large and heavy dimensions, of course with relatively very expensive costs and generally for the needs of laboratory procurement. Keywords: Oscilloscope, Electrical Signal, Portable, Electronic Measuring Instruments.